OPTIMIZATION OF CLIMATE CONDITION AND EFFECT OF MEDIA COMPOSITION TO SUCCESSFUL OF ACCLIMATIZATION OF RUBBER PLANTS ORIGINATED FROM SOMATIC EMBRYOGENESIS - Oktavia, Fetrina (Jurnal Penelitian Karet, 2020)
OPTIMASI KONDISI IKLIM DAN PENGARUH MEDIA TANAM TERHADAP KEBERHASILAN AKLIMATISASI TANAMAN KARET ASAL EMBRIOGENESIS SOMATIK Optimization of Climate Condition and Effect of Media Composition to Successful of Acclimatization of Rubber Plants originated from Somatic Embryogenesis   AbstractAcclimatization is a critical period in the multiplication of plants through tissue culture. Plantlets deaths due to changes of the environmental conditions from in vitro to ex vitro often occur during this period, so the effort is needed to manipulate the environmental conditions to be obtained optimum conditions. The research aims to optimize the temperature and humidity conditions and to see the effect of planting media composition suitable for acclimatization stage of rubber planting material from somatic embryogenesis in the greenhouse. Climate optimization in plastic tunnel was carried out using the fogging system. Experiment used 210 planlets of PB 260 clones originating from Cirad, France. Planlets were planted in 7 combination of grow media using a complete random design with three replication, and each replication consisted of 10 plant. Observations were conducted to the percentage of survival plants, high, diameter and number of leaves during acclimatization. Result showed that type of media influenced the survival ability of plants. The highest survival rate reached 90% was resulted on soil and mix of cocofiber, peat moss and zeolite media. Type of media did not give a significant effect to high, diameter and number of leaves of plants during two month acclimatization. The significant effect of media type were resulted on high of plants on three month after acclimatization. In the limitations conditions of  top soil availability, the mix of cocofiber, peat moss and zeolite can be used as a alternative of substitute media for rubber plant.Keywords: Hevea brasiliensis, rubber seedlings, tissue culture, juvenility, planting mediaAbstrak Aklimatisasi merupakan periode kritis dalam perbanyakan tanaman melalui kultur jaringan. Kematian planlet akibat terjadinya perubahan kondisi lingkungan dari in vitro ke ex vitro sering terjadi pada periode tersebut, sehingga perlu dilakukan upaya memanipulasi kondisi lingkungan untuk memperoleh kondisi yang optimum. Penelitian bertujuan untuk mengoptimasi kondisi suhu dan kelembapan serta melihat pengaruh komposisi media tanam yang sesuai untuk proses aklimatisasi bibit karet asal embriogenesis somatik di rumah kaca. Optimasi iklim dalam sungkup plastik dilakukan dengan menggunakan alat fogging system. Penelitian menggunakan 210 planlet klon PB 260 yang berasal dari Cirad, Perancis. Planlet ditanam pada 7 kombinasi media tumbuh menggunakan Rancangan Acak Lengkap dengan tiga ulangan dan setiap ulangan terdiri dari 10 tanaman. Pengamatan dilakukan terhadap persentase tanaman hidup, tinggi, diameter dan jumlah daun tanaman selama aklimatisasi. Pengamatan menunjukkan bahwa jenis media berpengaruh terhadap kemampuan tanaman bertahan hidup. Persentase tanaman bertahan hidup mencapai 90% ditemukan pada media tanah dan campuran cocofiber, gambut dan zeolit.  Jenis media tidak berpengaruh nyata terhadap tinggi, diameter dan jumlah daun tanaman selama dua bulan aklimatisasi. Pengaruh nyata jenis media tanam hanya ditemukan terhadap pertumbuhan tinggi tanaman 3 bulan setelah aklimatisasi. Dlam kondisi keterbatasan ketersediaan top soil, campuran media cocofiber, gambut dan zeolit dapat digunakan sebagai alternatif media pengganti tanaman karet.Kata kunci : Hevea brasiliensis, bibit karet, kultur jaringan, juvenilitas, media tanam